2020
DOI: 10.1016/j.tranon.2020.100832
|View full text |Cite
|
Sign up to set email alerts
|

Plocabulin, a novel tubulin inhibitor, has potent antitumor activity in patient-derived xenograft models of gastrointestinal stromal tumors

Abstract: The majority of patients with gastrointestinal stromal tumors (GIST) eventually become resistant with time due to secondary mutations in the driver receptor tyrosine kinase. Novel treatments that do not target these receptors may therefore be preferable. For the first time, we evaluated a tubulin inhibitor, plocabulin, in patient-derived xenograft (PDX) models of GIST, a disease generally considered to be resistant to cytotoxic agents. Three PDX models of GIST with different KIT genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…Apart from the antitubulin activity of the compound, preclinical work by Galmarini and colleagues demonstrated potent antiangiogenic properties, reflected by a strong reduction in vascular volume, both in vitro in the cultures and spheroids of human umbilical vein endothelial cells, and in vivo in a xenograft of lung adenocarcinoma [20]. Our recent in vivo study confirmed the strong vascular-disruptive potent antitumour effects of the drug in the patient-derived xenograft (PDX) models of gastrointestinal stromal tumours, a distinct, common histological subtype of STS [21]. Moreover, a phase I study demonstrated promising antitumour effects of plocabulin in patients with advanced colorectal adenocarcinoma, gastrointestinal stromal tumour and cervix, breast, thymus, lung and parotid adenocystic carcinoma [22].…”
Section: Introductionsupporting
confidence: 66%
“…Apart from the antitubulin activity of the compound, preclinical work by Galmarini and colleagues demonstrated potent antiangiogenic properties, reflected by a strong reduction in vascular volume, both in vitro in the cultures and spheroids of human umbilical vein endothelial cells, and in vivo in a xenograft of lung adenocarcinoma [20]. Our recent in vivo study confirmed the strong vascular-disruptive potent antitumour effects of the drug in the patient-derived xenograft (PDX) models of gastrointestinal stromal tumours, a distinct, common histological subtype of STS [21]. Moreover, a phase I study demonstrated promising antitumour effects of plocabulin in patients with advanced colorectal adenocarcinoma, gastrointestinal stromal tumour and cervix, breast, thymus, lung and parotid adenocystic carcinoma [22].…”
Section: Introductionsupporting
confidence: 66%
“…In the present study we have investigated the antiproliferative effect of plocabulin in a panel of HGSOC cell lines, including CDDP resistant scenario, and our results demonstrate that plocabulin has a dose-dependent potent cytotoxic activity, with IC 50 values within low nanomolar range. Other preclinical in vitro and in vivo studies have been done with plocabulin in endothelial cells ( 13 ), patient-derived colorectal cancer organoids, with dose responses very similar to ours ( 23 ), or gastrointestinal stromal tumor (GIST) patient-derived xenograft (PDX) mice ( 14 ). All of them show promising results enhancing the antitumor effect of plocabulin in different solid tumors, supporting the development of clinical trials to explore the activity of plocabulin in patients.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, antiangiogenic treatment with bevacizumab is approved in OC for first line and relapse settings. Preclinical studies have reported an antiangiogenic effect of plocabulin in GIST PDX ( 14 ), and also in endothelial cells, where it inhibits the migration and invasion abilities at picomolar concentrations that suppress microtubule dynamics but do not affect cell survival ( 13 ). To our knowledge, this is the first study to evaluate the effects of plocabulin on tumor cell invasion and migration, and together with the aforementioned studies, it demonstrates an important effect in the global process of metastasis, since it can inhibit the migration of tumor and endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cervical cancer, vadimezan (DMXAA) is the only flavonoid or VDA that has been tested in a clinical context [ 127 ]. Other agents are in development that have yet to be tested in clinical trials [ 128 , 129 , 130 ]; currently, it is too early to tell whether these will have a meaningful impact upon the therapeutic landscape.…”
Section: Angiogenesis Inhibitors In Gynecologic Cancers: Carving a Ne...mentioning
confidence: 99%